Basic Sanitation Analysis of Austin Resto Restaurant in Medan City - Agustina Friska (Paspama Institute, 2025)
The need for good sanitation is something that must be met in today's increasingly advanced era. With the realization of good basic sanitation, it is expected to reduce the occurrence of disease transmission, especially in vector-based, water- and food-borne diseases. This study aims to analyze the basic sanitation of the Austin Resto restaurant in Medan City in 2023. This study is a descriptive study with an observational design. The object observed in this study is the state of Basic Sanitation of the Austin Resto Restaurant including 7 variables, namely location and building variables, sanitation facility variables, kitchen, dining room and food warehouse variables, food and prepared food variables, food processing variables, food and prepared food storage variables, and equipment variables used. Data collection in this study is primary data obtained by direct observation of the infrastructure available at the research location and conducting observations using a restaurant hygiene and sanitation checklist sheet. The results of this study are the physical condition of the location and building with a percentage of 93.75% meet the requirements, restaurant sanitation facilities with a percentage of 66.92% do not meet the requirements, the kitchen, dining room and restaurant food warehouse with a percentage of 79% meet the requirements, the selection of restaurant food ingredients with a percentage of 100% meet the requirements, food processing 70% do not meet the requirements, storage of ready-made food with a percentage of 100% meet the requirements, transportation and serving of ready-made food with a percentage of 100% meet the requirements, food equipment used in the kitchen with a percentage of 60% do not meet the requirements. So it is hoped that the restaurant will pay more attention to the sanitation of the restaurant kitchen, food processing, equipment and food handlers and food handlers should take food processing sanitation courses, have health certificates, and health guidebooks so that the food and drinks sold are more hygienic.